Does Muscle Length Influence Regional Hypertrophy? A Systematic Review and Meta-Analysis - Varovic, Dorian; Wolf, Milo; Schoenfeld, Brad J; Steele, James; Grgic, Jozo; Mikulic, Pavle (International Journal of Sports Medicine, 2025)
The aim of this review was to examine how mean muscle length during resistance training (RT) influences regional muscle hypertrophy. Three databases were screened for relevant studies that manipulated muscle length through range of motion or exercise selection and evaluated regional muscle hypertrophy. Twelve studies conducted among young adults were included in the Bayesian meta-analysis. Standardized mean differences (SMDs) indicated trivial hypertrophic effects estimated with relatively high precision between proximal (25% muscle length; SMD: 0.05 [95% quantile interval QI:−0.07, 0.16]; exponentiated log-transformed response ratio [lnRR]: 0.57% [95% QI:−1.92%, 3.24%]), mid-belly (50% muscle length; SMD: 0.07 [95% QI:−0.02, 0.15]; exponentiated lnRR: 1.22% [95% QI:−0.77%, 3.22%]), and distal (75% muscle length; SMD: 0.09 [95% QI:−0.01, 0.19]; exponentiated lnRR: 1.88% [95% QI:−0.44%, 4.34%]) sites. The effects of RT at longer muscle lengths showed an increasing trend from proximal to distal sites. However, the percentage of posterior distributions falling within regions of practical equivalence was high across all sites. Our findings suggest that RT at both longer and shorter mean muscle lengths produces similar hypertrophic effects. Relatively small differences between “shorter” and “longer” mean muscle length (an average difference of 21.8% mean muscle length) between conditions/groups in the examined studies warrant caution when interpreting the findings.
Keywords: range of motion; resistance training; nonuniform hypertrophy